Effectiveness of interventions for the prevention of occupational violence against professionals in health services: a protocol for a systematic review - Caroline Vieira Cláudio Okubo; Renata Cristina Campos Pereira Silveira; Maria José Quina Galdino; Daiane Rubinato Fernandes; Aline Aparecida Oliveira Moreira; Júlia Trevisan Martins (BMJ Open)
Introduction Occupational violence affects several categories of workers; however, the health sector category has been considered at a high risk, exposing workers to physical and psychological abuse. Thus, occupational violence has decreased the quality of care in health service. This review aims to evaluate the effectiveness of interventions for the prevention and reduction of occupational violence against health professionals.Methods and analysis This protocol is consistent with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. Searches will be conducted in PubMed, Embase, Cochrane Library, LILACS, Web of Science, Scopus, CINAHL and LIVIVO along with a comprehensive review of grey literature. The search will be conducted on August 1 st 2020, without language and time restrictions. Following the eligibility criteria, two independent reviewers will select the titles and abstracts and subsequently screen the full articles. If necessary, a third reviewer will assess any disagreements. All references will be imported into EndNote, and any duplicates will be removed. The data will be extracted using an extraction-based form from Cochrane. Statistical analyses will be performed using the software Cochrane Review Manager, and a meta-analysis will be performed if possible for the statistical combination of at least two studies. The risk of bias of the randomised clinical trials will be evaluated by the Risk of Bias tool from Cochrane, and the risk of bias of the non-randomised intervention studies will be evaluated using the Downs and Black scale. The quality of the evidence and strength of the classification recommendations will be assessed by the Grading of Recommendations, Assessment, Development and Evaluation.Ethics and dissemination This review will not evaluate individual patient information and therefore does not require ethical approval. The results will be disseminated through publications in peer-reviewed journals, presentations at conferences and the doctoral thesis of the leading author.PROSPERO registration number CRD42018111383.